2003
DOI: 10.1002/jmv.10293
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of HBV and HCV infection in a paediatric oncology ward: Epidemiological investigations and prevention of further spread

Abstract: Hospital-acquired hepatitis B (HBV) and C virus (HCV) infections continue to occur despite increased awareness of this problem among the medical community. One hundred six patients were infected in a haematology oncology ward for children, over the time period 1996 to 2000. Serum samples from 45 such patients and 3 from infected medical personnel were used for nucleic acid amplification. HBV core, as well as HCV core and hypervariable region 1 (HVR1) nucleotide sequences, were analysed by phylogenetic tree ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
36
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 16 publications
4
36
0
3
Order By: Relevance
“…Immunocompromised adults and children with malignant diseases, who undergo various percutaneous procedures, have been involved in nosocomial outbreaks of HCV infection on a number of occasions (2,7,9,17,29,31,36). Among these patients, both disease-associated and iatrogenic immunosuppression may facilitate HCV transmission, even when contamination is minimal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Immunocompromised adults and children with malignant diseases, who undergo various percutaneous procedures, have been involved in nosocomial outbreaks of HCV infection on a number of occasions (2,7,9,17,29,31,36). Among these patients, both disease-associated and iatrogenic immunosuppression may facilitate HCV transmission, even when contamination is minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Among these patients, both disease-associated and iatrogenic immunosuppression may facilitate HCV transmission, even when contamination is minimal. In most of these nosocomial outbreaks, the epidemiological investigation failed to identify with certainty the source or mode of HCV transmission (2,9,17,29,36). This failure occurred mainly because the onset of infection is frequently asymptomatic, increases in ALT levels during chemotherapy are not necessarily attributable to hepatic infection, and the appearance of anti-HCV in immunocompromised individuals is delayed (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic analysis of HBV nucleotide sequences can provide evidence for a common source in some nosocomial outbreaks (19,20). In other reports on suspected nosocomial outbreaks, the investigators showed that the isolated strains were genetically unrelated and originated from different sources of infections (21,22). Recently, a large nosocomial outbreak of HBV was reported in Belgium.…”
mentioning
confidence: 99%